Líbano en la encrucijada: las repercusiones de la guerra Israel-Hezbollah sobre el escenario político libanés - Sierra Kobeh, María de Lourdes (Revista Mexicana de Política Exterior, 2022)
The war between Israel and Hezbollah, and the repercussions it has had on Lebanon’s political scene, is the topic of this article by María de Lourdes Sierra Kobeh. This recent confrontation is but part of a complex web of conflicts that have been several years in the making within the region and that have since spread beyond its borders, played out against the backdrop of the so-called “war on terrorism” instigated by the Bush administration in the aftermath of the September 11 terrorist attacks. More than a year and a half has passed since the clash between Israel and Hezbollah, marking the onset of a new political crisis for Lebanon since November 2006, as a result of the power struggle between the Lebanese government, headed by Fouad Siniora, and opposition forces spearheaded by Hezbollah, a Lebanese-based Shi’a Islamic organization. In a worst-case scenario, if not resolved, this conflict could lead to the outbreak of another civil war. So as to give us an idea of what exactly is at stake here, Sierra Kobeh analyzes the roots of the crisis, contributing factors and the agendas of the two blocs involved. The author then follows this up with an analysis of the recent war between Israel and Hezbollah in the context of the historical development of Lebanon —on whose soil the battle was waged—, underscoring the consequences the war has had on the country’s home front.